Evaluating body roundness index and systemic immune inflammation index for mortality prediction in MAFLD patients - Di Zeng; Qingyue Zeng; Shuangqing Li; Jiong Lu; Nansheng Cheng (Scientific Reports)
Abstract Metabolic dysfunction-associated fatty liver disease (MAFLD) is a major cause of liver-related morbidity and mortality, contributing to both cardiovascular and non-cardiovascular deaths. The Body Roundness Index (BRI) and Systemic Immune-Inflammation Index (SII) have emerged as predictors of adverse outcomes in metabolic diseases. This study investigates the association between BRI, SII, and mortality risk in MAFLD patients. A nationwide retrospective cohort study was conducted using data from the NHANES database (January 1999–December 2018), including patients diagnosed with MAFLD. BRI and SII were calculated at baseline. Cox proportional hazards models assessed the association between these indices and all-cause, cardiovascular, and non-cardiovascular mortality, adjusting for confounders. Among 12,435 participants diagnosed with MAFLD, 3,381 (27.2%) were classified into the low BRI and low SII group, 2,889 (23.2%) into the low BRI and high SII group, 2,802 (22.5%) into the high BRI and low SII group, and 3,363 (27.1%) into the high BRI and high SII group. Compared to the low BRI and low SII group, the high BRI and high SII group demonstrated significantly higher all-cause mortality, with an adjusted hazard ratio (HR) of 1.89. For cardiovascular mortality, the HR was 2.31, while for non-cardiovascular mortality, the HR was 1.78. The high BRI and high SII cohort exhibited the highest risk of all-cause mortality, cardiovascular mortality, and non-cardiovascular mortality. BRI and SII are independent predictors of mortality in MAFLD patients, and their combined use enhances risk stratification. Integrating these indices into clinical practice could improve personalized management strategies and outcomes in this high-risk population.